1T1R Nonvolatile Memory with Al/TiO2/Au and Sol-Gel-Processed Insulator for Barium Zirconate Nickelate Gate in Pentacene Thin Film Transistor - Ke-Jing Lee (Materials, 2017)
A one-transistor and one-resistor (1T1R) architecture with a resistive random access memory (RRAM) cell connected to an organic thin-film transistor (OTFT) device is successfully demonstrated to avoid the cross-talk issues of only one RRAM cell. The OTFT device, which uses barium zirconate nickelate (BZN) as a dielectric layer, exhibits favorable electrical properties, such as a high field-effect mobility of 2.5 cm2/Vs, low threshold voltage of −2.8 V, and low leakage current of 10−12 A, for a driver in the 1T1R operation scheme. The 1T1R architecture with a TiO2-based RRAM cell connected with a BZN OTFT device indicates a low operation current (10 μA) and reliable data retention (over ten years). This favorable performance of the 1T1R device can be attributed to the additional barrier heights introduced by using Ni (II) acetylacetone as a substitute for acetylacetone, and the relatively low leakage current of a BZN dielectric layer. The proposed 1T1R device with low leakage current OTFT and excellent uniform resistance distribution of RRAM exhibits a good potential for use in practical low-power electronic applications.